Self- Sufficiency in Agricultural and Industrial Production in Indian Economy-A Study - Prabhuswamy, B. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This paper presents an overview of Self- sufficiency in agricultural and industrial production in Indian economy-a study.
Keywords: Agricultural; industrial; production; economy; population; employability; challenges; national; international; global context